Association of vitamin B1 with cardiovascular diseases, all-cause and cardiovascular mortality in US adults - Wen, He; Niu, Xiaona; Zhao, Ran; Wang, Qiuhe; Sun, Nan; Ma, Le; Li, Yan; Zhang, Wei (Frontiers in Nutrition, 2023)
Background The correlation between dietary vitamin B1 intake and cardiovascular diseases, as well as the all-cause and cardiovascular-associated mortality, is not well known. A large-scale data pool was used to examine the aforementioned correlations of Vitamin B1. Methods This paper analyzed the dietary data from the survey conducted by National Health and Nutrition Examination (NHANES; 1999–2018). The correlation of vitamin B1 intake in each quartile with cardiovascular diseases such as hypertension, coronary heart disease, myocardial infarction and heart failure was analyzed using multivariate logistic regression models. The hazard ratios for dietary vitamin B1 intake in each quartile, along with all-cause and cardiovascular-associated mortality, were performed using multivariate cox regression analysis, setting the lowest quartile (Q1) as a reference. The restricted cubic spline (RCS) method was used to study the nonlinear relationship. Subgroup stratification and sensitivity analyses were used to further investigate the association between them. Results The study enrolled 27,958 subjects (with a mean follow-up time of 9.11 years). After multivariate adjustment, dietary vitamin B1 intake was significantly associated with hypertension, heart failure and cardiovascular mortality, with the most significant association in quartile 4 (Q4) of vitamin B1 intake. The results of the restricted cubic spline showed that vitamin B1 intake was nonlinearly associated with hypertension, whereas it was linearly associated with heart failure and cardiovascular mortality. Meanwhile, a dose–response correlation was observed, indicating that increased vitamin B1 intake leads to reduced risk of both cardiovascular prevalence and mortality. The stratified analysis showed that the correlation between age ≥ 50 years, overweight, smoking history, drinking history and dyslipidemia were more significant in male patients. The associations remained similar in the sensitivity analyses. Conclusion The large NHANES-based studies indicate a gradual trend toward decreasing the risk of hypertension and heart failure prevalence and cardiovascular mortality with increasing dietary vitamin B1 intake. This association is especially significant in elderly-aged men, overweight individuals, smokers, drinkers, and dyslipidemia patients.